Genomic analyses reveal two distinct lineages of Corynebacterium ulcerans strains. (September 2018) - Subedi, R.; Kolodkina, V.; Sutcliffe, I.C.; Simpson-Louredo, L.; Hirata, R.; Titov, L.; Mattos-Guaraldi, A.L.; Burkovski, A.; Sangal, V.
Abstract: Corynebacterium ulcerans is an important zoonotic pathogen which is causing diphtheria-like disease in humans globally. In this study, the genomes of three recently isolated C. ulcerans strains, 4940, 2590 and BR-AD 2649, respectively from an asymptomatic carrier, a patient with pharyngitis and a canine host, were sequenced to investigate their virulence potential. A comparative analysis was performed including the published genome sequences of 16 other C. ulcerans isolates. C. ulcerans strains belong to two lineages; 13 strains are grouped together in lineage 1, and six strains comprise lineage 2. Consistent with the zoonotic nature of C. ulcerans infections, isolates from both the human and canine hosts clustered in both the lineages. Most of the strains possessed spaDEF and spaBC gene clusters along with the virulence genes cpp, pld, cwlH, nanH, rpfI, tspA and vsp1 . The gene encoding Shiga-like toxin was only present in one strain, and 11 strains carried the tox gene encoding the diphtheria-like toxin. However, none of strains 4940, 2590 and BR-AD 2649 carried any toxin genes. These strains varied in the number of prophages in their genomes, which suggests that they play an important role in introducing diversity in C. ulcerans. The pan-genomic analyses revealed a variation in the number of membrane-associated and secreted proteins that may contribute to the variation in pathogenicity among different strains.